2018
DOI: 10.1016/j.aprim.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de hipovitaminosis D y factores asociados en la edad infantojuvenil

Abstract: There is a high prevalence of hypovitaminosisD in juvenile populations. being female, pubertal age, autumn, winter and spring seasons, severe obesity, and living in urban areas are factors associated to hypovitaminosisD. Consideration should be given to the administration of vitamin supplements and/or the increase in the ingestion of natural vitaminD dietary sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
3
0
4
Order By: Relevance
“…These differences could be due to several factors, the first of which is the use of different cutoffs to establish low levels of Vit D between studies. For instance, Durá-Travé et al [ 31 ] defined hypovitaminosis D according to the U.S. Endocrine Society criteria: deficiency and insufficiency levels of Vit D below 30 ng/mL; in our study, a value of Vit D between 21 and 29 ng/mL was defined as sufficient for bone health based on Holick’s cutoffs [ 19 ]. The second reason is the inclusion of pubertal individuals who showed higher levels of Vit D deficiency in comparison with prepubertal children [ 8 , 32 ].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These differences could be due to several factors, the first of which is the use of different cutoffs to establish low levels of Vit D between studies. For instance, Durá-Travé et al [ 31 ] defined hypovitaminosis D according to the U.S. Endocrine Society criteria: deficiency and insufficiency levels of Vit D below 30 ng/mL; in our study, a value of Vit D between 21 and 29 ng/mL was defined as sufficient for bone health based on Holick’s cutoffs [ 19 ]. The second reason is the inclusion of pubertal individuals who showed higher levels of Vit D deficiency in comparison with prepubertal children [ 8 , 32 ].…”
Section: Discussionmentioning
confidence: 96%
“…Vit D deficiency has been shown to be highly prevalent in children [ 28 , 29 ]; hypovitaminosis is a common feature in overweight and obese children or pediatric populations with severe obesity [ 30 , 31 ]. For example, Durá-Travé et al [ 31 ] reported that the prevalence of hypovitaminosis D was 60.4% in Spanish children and adolescents. Similarly, Viana et al [ 8 ] found that the prevalence of Vit D deficiency was in a higher proportion in pubertal individuals (71.8%) in comparison with prepubertal children (62.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La vitamina D (VitD) es una prohormona esencial, que cumple un rol determinante en el metabolismo óseo, interactuando con la absorción intestinal y reabsorción renal de calcio; su deficiencia, produce efectos en la mineralización ósea, siendo su presentación clínica más grave, el raquitismo en los niños (2). En pediatría, la deficiencia se ha relacionado con otros condiciones clínicas como desnutrición, obesidad(3), síndrome metabólico, diabetes, cáncer, infecciones de vías respiratorias y problemas del sistema inmune (4,5).…”
Section: Introductionunclassified
“…Health and Nutrition Examniation Survey) entre 2007-2010, ayant concerné 15650 personnes de tout âge, dont 1855 d'âge scolaire(6-11 ans), arapporté un taux moyen de la Vit.D entre 22,96 et 32,12 ng/mL (valeurs variant selon l'ethnie)[9]. A Punta Arena au Chili, une étude sur 108 enfants âgés versus 44,6% de suffisance[13]. Andıran et al, dans une cohorte turque, ont rapporté une moyenne globale de 20,5±8,7 5-10 ng/mL chez les 5-10 ans[14].…”
unclassified